Economic issues of innovation clusters-based industrial policy : a critical overview - B. G. Jean Jacques Iritié (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Criticisms vis-à-vis cluster policy are numerous, often confusing and really unhelpful; while some authors systematically question the merits, others on the contrary play a genuine role of counsel in his favour. This paper attempts to refocus the debate and analyses the economic issues, impacts and implications of the innovation clusters policy. To do this, we take a critical view of the literature on clusters, focusing on analysis of the effects of three industrial dynamics in perpetual movement within clusters, especially research and development, industrial location and technology cooperation. We assume that innovation cluster "potentiates", by a synergistic action, the beneficial effect of each of these three industrial dynamics in favour of localised firms. However, it appears from the analysis that the hopes and expectations invested in cluster policy must be reconsidered and relativised. So the reasons for the rising power of cluster policies must be sought elsewhere than in a necessarily consensual and tangible evidence of positive impacts of clusters.
Additional information: Revised and expanded of LADEG Working Paper No. 002/2015
Keywords: O25; O30; R10; 330; cluster; innovation; competitiveness pole; research and development; industrial location; technology cooperation; localised knowledge spillovers; LKS; epistemic communities